Effect of Fall on Medical Costs among Elderly Inpatients; A Case-Study in Iran - afsaneh fallahi; leila riahi; aniseh nikravan (Shahid Sadoughi University of Medical Sciences, 2021)
Objective: Falls are the main cause of injuries and death among the elderly and lead to using medical services. This study aimed to assess the effect of falls on medical costs among elderly inpatients. Methods: This retrospective cross-sectional study was done in a public hospital (heart center) in Qazvin, Iran. In this study, 79 medical records of the elderly who had experienced in-hospital falls and 79 medical records in control group with similar characteristics who had not experienced in- hospital falls during 2016-2019. The data, including the elderly age, sex, fall characteristics, and all hospital costs related to falls were gathered from hospital accident forms, medical records, nursing reports, and official data banks. The overall costs of services provided for fallen elderly were compared with the control group. The data were analyzed by SPSS software, version 22, using Chi-square and paired sample t-test. P<0.05 was considered statistically significant. Results: Total cost of all services provided for the elderly during their hospitalization was 106.596$ (base year: 2019, $1=42500 IRR), of this amount 8.600$ (8.06%) was related to the services due to in-hospital falls. The highest costs were related to treatment services (40%), diagnostic services (33%), visits (21%) and consultation (6%). The difference between the case and control groups was 7.310$. The elderly falls significantly increased medical costs by 8.06% (P≤0.01). Conclusions: Even falls that do not lead to serious injuries waste medical services and increase hospital costs by making changes in treatment methods and increasing the length of hospital stay.